OPTIMIZATION OF CHOICE OF MELTING FACILITIES - S. M. Bokareva; L. E. Rovin (Литьë и металлургия)
The problem of optimization of right out fits choice at reconstruction of casthouses is considered. Introduction of the system of rating indices is offered.